THE LIFE OF THOMAS MORE AND HIS ‘’UTOPIA’’ - Yusupxojayeva Sevinch Alisher qizi; Kenjayeva Muxlisa Bahodirovna (TADQIQOTLAR.UZ, 2024)
Abstract: Sir Thomas More, also known as Saint Thomas More. In 1516, Sir Thomas More first used the phrase utopia.It was created by More by combining the Greek terms for "not" (ou) and "place" (topos), meaning "nowhere."More's Utopia, a work of fiction about an ideal island community, was written as a Humanist movement project.In Greek, utopia signifies nowhere.Raphael Hytloday tells the tale of Utopia as narrated by More.Hytloday translates to "talker of nonsense" from Greek.